Strategi Public Relations dalam Program Berbagi Helm Gratis untuk Membangun Citra Polres Metro Jakarta Barat - Yudistira Raden Syahputra; Istisari Bulan Lageni; Tria Patrianti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of public relations strategies in the “Berbagi Helm Gratis” program conducted by the West Jakarta Metro Police as an institutional effort to strengthen public trust and develop a positive organizational image. Using a qualitative case study approach, the research explores how communication strategies are designed and implemented within a public safety initiative integrated into the 2024 Operation Zebra Jaya campaign. Empirical data were collected through field observations, in-depth interviews with institutional actors, and documentation of program activities. The findings indicate that the distribution of helmets functions not only as a traffic safety intervention but also as a strategic communication instrument that facilitates interaction between police officers and citizens. The program demonstrates how community-based engagement can humanize institutional authority and reinforce perceptions of service orientation within law enforcement institutions. Furthermore, the integration of direct communication practices with digital public relations channels strengthens the visibility and credibility of institutional initiatives. The study highlights the importance of socially embedded public relations strategies in fostering institutional legitimacy and improving public perception toward police organizations.